Perikatan dalam Kontrak:Perlindungan Hukum bagi Pekerja dan Pengusaha - Rika Widiastuti; Syalsa Nabila Anisa; Muhammad Syahdan Daniyal (Letterlijk, 2024)
Legal protection for workers in Indonesia is regulated in Law Number 13 of 2003 concerning Employment. The basic policy in Labor Law is to protect the weak party, in this case the worker or laborer, from the arbitrariness of the employer or entrepreneur. However, in reality, since the enactment of Law Number 13 of 2003 concerning Employment, many people have complained about the certainty of their employment status due to the fixed-term employment contract system. However, with the issuance of Law Number 11 of 2020 concerning Job Creation, there are many concerns that the implementation of work with Specific Time Agreement (PKWT) status will be further relaxed. The formulation of the problem discussed in this article is what is the form of legal protection for workers according to the Job Creation Law and what is the form of legal protection for workers according to Law Number 13 of 2003. The results of the research show that Law Number 13 of 2003 concerning Employment provides various forms of legal protection for workers in Indonesia. This protection includes the right to decent wages, reasonable working and rest periods, as well as social security such as health insurance, old age security and work accident insurance. Meanwhile, the Job Creation Law is considered to be more detrimental to workers or laborers, as if there is bias towards certain parties. Indirectly, this proves that the Job Creation Law does not have the principles of justice that it should be because in several articles what is needed for workers or laborers is actually omitted.